The value of the expression
[(sec2 theta - 1) (1 - cosec2 theta )] is :
(A) – 1 (B) 1 (C) 0 (D) 2
Answers
Answered by
3
Answer:
1, option ( B ) is right
Step-by-step explanation:
Given---> ( Sec²θ - 1 ) ( 1 - Cosec²θ )
To find---> Value of given expression.
Solution---> We know that
1 + tan²A = Sec²A
=> tan²A = Sec²A - 1
We know that,
1 + Cot²A = Cosec²A
=> Cot²A = Cosec²A - 1
Now returning to original problem
( Sec²θ - 1 ) ( Cosec²θ - 1 )
Putting Sec²θ - 1 = tan²θ and Cosec²θ - 1 = Cot²θ , we get.
= ( tan²θ ) ( Cot²θ )
We know that Cotθ = 1 / tanθ , using it here we get,
= tan²θ ( 1 / tan²θ )
tan²θ cancel out from numerator and denominator
= 1
Answered by
0
Answer:
Option is (b) the correct..
Similar questions
English,
7 months ago
Social Sciences,
7 months ago
Chemistry,
1 year ago
Math,
1 year ago
Science,
1 year ago